Survey of Lifestyle Patterns on the Health of Physical Education Students of the 2023 Class B Academic Year 2025/2026 - Mohd Akhbar Abdullah; ME Winarno (CV. SAMODRA INSAN PENA, 2026)
This study aims to examine the healthy lifestyle patterns of Physical Education students and to identify the dimensions requiring priority attention. A quantitative descriptive survey design was employed, involving 38 students selected through total sampling. Data were collected using a Likert-scale questionnaire covering four dimensions of healthy lifestyle behavior based on the World Health Organization framework: physical activity, nutrition, sleep patterns, and general health practices. Data analysis was conducted using descriptive statistics to obtain mean scores, percentages, and categorical classifications based on the Healthy Lifestyle Assessment Toolkit. The results showed that 52.63% of students were categorized as having a good healthy lifestyle, with a mean score of 101.47 (69.98% of the maximum score). However, analysis across dimensions revealed that sleep patterns had the lowest level of achievement (65.49%), indicating an imbalance in lifestyle implementation. These findings suggest that although awareness of healthy lifestyle behaviors exists among students, their consistent application across all dimensions remains limited. Therefore, improving sleep quality and implementing integrated, campus-based health promotion programs are essential to achieving a more balanced and sustainable healthy lifestyle among Physical Education students.